1986
DOI: 10.1093/jac/17.suppl_c.149
|View full text |Cite
|
Sign up to set email alerts
|

Timentin in the antimicrobial treatment of nosocomial and polymicrobial infections

Abstract: The combination of ticarcillin and clavulanic acid (Timentin) was used in a nonrandomized open study in 28 patients with severe nosocomial infections. The infections were polymicrobial in 19 cases. Ten patients were bacteraemic and all were severely ill, receiving mechanical ventilation and with at least one organ system failure. Seventeen patients were treated with Timentin alone, 11 with a combination of Timentin and aminoglycosides. Timentin was used empirically, before identification of the bacteria in 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…The management of post‐operative peritonitis is different, in that the bacteria are frequently resistant to antimicrobial therapy, and it has been shown that inadequate antimicrobial therapy prolongs hospitalisation and is associated with clinical failure and a higher mortality rate [2,21]. In this context, empirical antimicrobial therapy is based on the local ecology, and frequently requires the use of expanded‐spectrum multidrug regimens that include an aminoglycoside or a quinolone, or a carbapenem and vancomycin [7,22]. Nosocomial non‐post‐operative peritonitis represents a particular entity that, until recently, was classified as post‐operative peritonitis with a high frequency of resistant bacteria [7,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of post‐operative peritonitis is different, in that the bacteria are frequently resistant to antimicrobial therapy, and it has been shown that inadequate antimicrobial therapy prolongs hospitalisation and is associated with clinical failure and a higher mortality rate [2,21]. In this context, empirical antimicrobial therapy is based on the local ecology, and frequently requires the use of expanded‐spectrum multidrug regimens that include an aminoglycoside or a quinolone, or a carbapenem and vancomycin [7,22]. Nosocomial non‐post‐operative peritonitis represents a particular entity that, until recently, was classified as post‐operative peritonitis with a high frequency of resistant bacteria [7,22].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, empirical antimicrobial therapy is based on the local ecology, and frequently requires the use of expanded‐spectrum multidrug regimens that include an aminoglycoside or a quinolone, or a carbapenem and vancomycin [7,22]. Nosocomial non‐post‐operative peritonitis represents a particular entity that, until recently, was classified as post‐operative peritonitis with a high frequency of resistant bacteria [7,22]. However, a large multicentre study in France has shown that the microbiological characteristics of nosocomial non‐post‐operative peritonitis mimic those of community‐acquired peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Physicians have to assume that these infections share several clinical and microbiological characteristics in common with other nosocomial infections due to preoperative hospitalization and colonization with nosocomial flora. 5 However, these patients might also present a number of similarities with community-acquired intra-abdominal infections, such as absence of previous surgery or similar etiologies of intra-abdominal infection.…”
mentioning
confidence: 99%
“…[8,9] Pre-operative antibiotic therapy can reduce the incidence of surgical site infections [14,15]. The most common organisms causing surgical site infections are MRSA, Staphylococcus epidermidis, enteric gram+ve cocci [16,17], gram-ve bacilli and anaerobes [18].…”
Section: Introductionmentioning
confidence: 99%